IMF Survey, Volume 36 Issue 11. (IMF Survey; IMF Survey, 2007)
IMF plan to cut imbalances; IMF clarifies aid role; world growth update; financial globalization; growth in Africa; low-income countries need fiscal reform; Central America seeks stronger growth; IMF surveillance framework; news briefs.